Núcleo de cohesión social con miras a la reinserción y la resocialización: establecimiento penitenciario de mediana seguridad de Riohacha (2022)
This thesis examines two innovative research topics, which are: (1) spatial design directly affects the development of good mental health; and (2) the high energy efficiency requirements of the institutions, which leads us to propose a medium-security prison model whose physical space directly affects the activities and behavior of people (including the penitent and the agents who surround him), in order to improve the quality of life during and after his penance, as well as, the reduction of energy efficiency through lighting, heating and ventilation systems with sustainable and cyclical parameters, while guaranteeing a low maintenance environment